2020
DOI: 10.1002/ldr.3613
|View full text |Cite
|
Sign up to set email alerts
|

The effects of land degradation on plant community assembly: Implications for the restoration of the Tibetan Plateau

Abstract: Understanding how biotic and abiotic filters drive plant distributions is critical for informing restoration efforts of degraded lands. However, it remains unclear whether or not it is possible to develop efficient restoration strategies that are based on field investigations? Here, we conducted a field-based investigation along a land degradation gradient on the Tibetan Plateau. Along this gradient, we compared species composition, Pianka's niche overlap, and total aboveground biomass among grasses, sedges, l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…With the increasing desertification, grassland herbs are gradually replaced by shrubs, semi‐shrubs, and forbs, and the dominant species finally changed into sparsely distributed drought‐ and barren‐tolerant annual sandy plants (Li, Jia, & Dong, 2006; Schlesinger et al, 1990). During this process, niche overlap decreases with increasing desertification severity (Luo et al, 2020), accompanied by decreasing plant productivity and diversity (Li, Zhao, et al, 2006). For example, previous studies in Ethiopia suggested that the soil seed bank would be reduced with the strengthening of degradation, and the severely degraded ecosystem could not even maintain an adequate soil seed bank (Kassahun et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…With the increasing desertification, grassland herbs are gradually replaced by shrubs, semi‐shrubs, and forbs, and the dominant species finally changed into sparsely distributed drought‐ and barren‐tolerant annual sandy plants (Li, Jia, & Dong, 2006; Schlesinger et al, 1990). During this process, niche overlap decreases with increasing desertification severity (Luo et al, 2020), accompanied by decreasing plant productivity and diversity (Li, Zhao, et al, 2006). For example, previous studies in Ethiopia suggested that the soil seed bank would be reduced with the strengthening of degradation, and the severely degraded ecosystem could not even maintain an adequate soil seed bank (Kassahun et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Land degradation increased the R/S ratio of alpine meadows in the QTP due to a significant decrease in aboveground biomass and a weak change in belowground biomass (Zhang et al, 2019). Moreover, the negative effects of land degradation on plant species richness, plant composition, and plant competition have been widely studied in the QTP (Wang et al, 2014;Tang et al, 2015;Luo et al, 2020;Peng et al, 2020). However, it is still unclear whether the land degradation would change the role of aboveand belowground competition in regulating the R/S ratio.…”
Section: Introductionmentioning
confidence: 99%